2018
DOI: 10.1159/000490370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low-Dose/High-Frequency Training on Real-Life Neonatal Resuscitation in a Low-Resource Setting

Abstract: Background: As intrapartum-related events represent a quarter of all neonatal deaths, education on neonatal resuscitation is a critical priority. Objective: To assess the impact of a low-dose/high-frequency neonatal resuscitation training on clinical practice of midwives in a low-resource setting. Methods: Eight months after a modified Neonatal Resuscitation Program (NRP) course, we implemented a low-dose/high-frequency training for midwives at Beira Central Hospital, Mozambique. The training lasted 6 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…In addition, there is a paucity of literature on Liberia-specific neonatal resuscitation training, and this study provides some preliminary evidence. Studies conducted in other parts of Africa with similar resource constraints also show positive results in knowledge improvement [14,15,16].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, there is a paucity of literature on Liberia-specific neonatal resuscitation training, and this study provides some preliminary evidence. Studies conducted in other parts of Africa with similar resource constraints also show positive results in knowledge improvement [14,15,16].…”
Section: Discussionmentioning
confidence: 96%
“…Research in learning theory suggests that a combination of testing and spaced repetition may be the most effective for learning retention and may enhance the learner’s ability to generalize their knowledge to new situations [17]. While the optimal spacing has not been established in the literature for neonatal resuscitation, Cavicchiolo et al [16] in Mozambique suggest low-dose/high-frequency training with an adapted NRP curriculum may improve initiation and time to resuscitation [16]. Further work should focus on establishing an evidence base for the optimum spacing and delivery method for neonatal resuscitation training, as sustainability will be crucial to enacting a lasting effect on the overall mortality rate in Liberia.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of in-service training showed that targeted, repeated interventions lead to better training outcomes [39]. A recent study in Mozambique found that LDHF training on newborn resuscitation helped improve midwife performance [40], and in Tanzania a supportive intervention to HBB resulted in higher retention of newborn resuscitation skills [23]. A cluster randomized trial in Ghana found that in health facilities using an onsite, LDHF approach to training on intrapartum care, the relative risk of newborn mortality and intrapartum stillbirth significantly declined up to a year following training, leading the authors to recommend use of this training approach [41].…”
Section: Discussionmentioning
confidence: 99%
“…Shaimaa Abuelnoor Ahmed Abdelghany 2 Serena Calgaro 2,3 Amir Hussein Abubacar Seni 4 Bonifacio Rodriguez Cebola 4 Giovanni Putoto 3 Daniele Trevisanuto 2…”
Section: Ack N Owled G Em Entsmentioning
confidence: 99%